La “terminación” del contrato por causas intrínsecas y extrínsecas ¿Un régimen unitario o diferenciado de efectos? (Tema Central) - Momberg Uribe, Rodrigo (2025)
This paper addresses the question of the reasonableness of a unitary system of effects for contractual termination in a broad sense, encompassing both intrinsic and extrinsic causes. To this end, it undertakes a comparative analysis of the regulation of the effects of nullity and termination for breach in two normative models: one “traditional”, the Civil Code of Bello, and the other “modern”, the UNIDROIT Principles of International Commercial Contracts. The conclusion suggests that maintaining a differentiated regime, as both texts do, is appropriate. Consequently, doctrinally supporting such a broad notion of “contractual termination” proves neither useful as a basis for a conceptual framework nor as a foundation for a normative regime.